A longitudinal study of Web pages continued: a consideration of document persistence. Web documents, Half-life, Linkrot, Persistence, Web citations - Wallace Koehler (Information Research: An International Electronic Journal)
It is well established that Web documents are ephemeral in nature. The literature now suggests that some Web objects are more ephemeral than others. Some authors describe this in terms of a Web document half-life, others use terms like 'linkrot' or persistence. It may be that certain 'classes' of Web documents are more or less likely to persist than are others. This article is based upon an evaluation of the existing literature as well as a continuing study of a set of URLs first identified in late 1996. It finds that a static collection of general Web pages tends to 'stabilize' somewhat after it has 'aged'. However 'stable' various collections may be, their instability nevertheless pose problems for various classes of users. Based on the literature, it also finds that the stability of more specialized Web document collections (legal, educational, scientific citations) vary according to specialization. This finding, in turn, may have implications both for those who employ Web citations and for those involved in Web document collection development.